"Geländer" macrocycles: Synthesis, chirality and racemisation barriers. Issue 4 (24th January 2019) - Lar, Claudia; Moisӑ, Mӑdӑlina Elena; Bogdan, Elena; Terec, Anamaria; Hӑdade, Niculina Daniela; Grosu, Ion; David, Luminiţa; Paizs, Csaba; Grosu, Ioana Georgeta
Graphical abstract: Highlights: Easy access to original oxime-based macrocyclic biphenyl with remarkable enantiomers' stability. The barriers for racemisation determined by chiral HPLC and DHPLC methods. Only a weak influence of the size of the macrocycles on the racemisation barriers noticed. A high increase in racemisation barriers by introduction of additional rigid units in the macrocycle. Abstract: A new class of axially-chiral o, o ′-bridged biphenyls containing etheroxime chains was obtained in good yields by the macrocyclisation reaction of o, o ′-diformylbiphenyl dioxime with several ditosylated or dibrominated reagents. In all cases the enantiomers of the compounds were separated by HPLC using a chiral column (Chiralpack IC) and the stability of the enantiomers (barriers of racemisation) was investigated employing chiral HPLC or chiral Dynamic HPLC techniques. A slight influence on the barrier to rotation was noticed when the enantiomerisation was performed in the presence of suitable alkali cations.